2012
DOI: 10.1097/wco.0b013e328355aa94
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain networks in movement disorders

Abstract: Purpose of review Different neuroimaging techniques have been used to identify disease-specific functional brain networks in Parkinson’s disease, atypical parkinsonian syndromes, and other movement disorders. This review highlights recent advances in network imaging and its clinical applications in movement disorders. Recent findings Positron emission tomography and functional MRI studies have revealed distinct, abnormal metabolic brain networks and altered interregional connectivity in Parkinson’s disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 83 publications
0
32
0
Order By: Relevance
“…These previous studies suggested regional abnormalities in the basal gangliathalamo-cortical circuitry in PKD, yet are limited to regional alterations, unable to manifest the functional connectivity related to this circuitry. Nowadays movement disorders have been viewed as circuitry disorders which are not confined to localized structure or functional abnormalities [18]. Robust disease and symptom specific functional networks have been identified in movement disorders using different paradigms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies suggested regional abnormalities in the basal gangliathalamo-cortical circuitry in PKD, yet are limited to regional alterations, unable to manifest the functional connectivity related to this circuitry. Nowadays movement disorders have been viewed as circuitry disorders which are not confined to localized structure or functional abnormalities [18]. Robust disease and symptom specific functional networks have been identified in movement disorders using different paradigms [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This patient presented with multifocal myoclonus occurring immediately following a right ACA territory stroke which had not been reported before [1]. The presence of multifocal involuntary movement following unilateral brain infarct may be explained by the recent advances in functional brain imaging which suggests that although the histopathological hallmark of movement disorders is located in the basal ganglia, they can be caused by alterations within functional whole brain networks rather than localized neurodegeneration [9].…”
mentioning
confidence: 86%
“…Movement disorders, however, are increasingly recognized to arise from abnormalities of neuronal circuitry rather than localized, circumscribed lesions [42]. The cerebellum has extensive bidirectional circuitry projections to an array of brainstem nuclei and the cerebral cortex that modulate and refine motor activities [43e45].…”
Section: Cerebellar Projectionsmentioning
confidence: 99%
“…Indeed, investigators speculate that a "non-optimally wired brain" [9], i.e., a brain with aberrant connectivity, may be the pathologic substrate of BIND [9,13]. Anatomical and functional connectivity using advanced neuroimaging techniques have identified specific alterations in functional brain networks in other brain disorders [42] and as a function of sex [67] and age [68]. These techniques may be able to identify some of the cerebellar and striatal pathways that are presumed to be altered in kernicterus and BIND patients.…”
Section: Advanced Neuroimaging and Bilirubin-induced Cns Injurymentioning
confidence: 99%